Influential Factor Affecting Consumer’s Satisfaction to Get Service from New Private Hospital in Bangkok - Laophanitcharoen, Jutamas; Boonyasopon, Teerawat; Pichitkarnkar, Thanyathip (Rajapark Journal, 2023)
This study has the objectives to investigate the factors that influence the satisfaction of customers who get service from new private hospital in Bangkok. Also study the satisfaction level of customers who get service from new private hospital in Bangkok. The study indicated that marketing mix factors (7P’s) that affect the satisfaction of customers who get service from new private hospital in Bangkok, the greatest factors being people, physical evidence, followed by process. On the other hand, customers satisfied in marketing mix of customer’s view (7C’s), sort descending factors; caring, completion, followed by comfort. According to the study of demographics that affect the satisfaction of customers who get service from new private hospital in Bangkok, the study indicated that the differences of gender, age, and occupation don’t affect to the satisfaction of customers who get service from new private hospital in Bangkok. Meanwhile, the difference of education level and average monthly income affect to the satisfaction of customers who get service from new private hospital in Bangkok.